Performance and genetic variability among tropical sweet corn inbred lines developed in Malaysia - Rahim, Nur Shila (2015)
A study was conducted to compare the performance of 27 tropical sweet corn (Zea mays L. saccharata) inbred lines, to estimates heritability of important traits measured, to determine correlations among the traits and to find out the genetic variability among the inbred lines evaluates based on their agronomic characteristics. The study was conducted in Randomized Complete Block Design (RCBD) with tree replications, at Field 16, Universiti Putra Malaysia (UPM). The inbred lines showed significant variation in agronomic performance. Among the inbred lines, FTT-1 was found to have the highest husked and dehusked ear yield (15,872 kg/ha), highest husked and dehusked ear weight (15,819 kg/ha), highest dehusked ear diameter (45.58 mm) and highest number kernel rows per ear (17.80). Inbred HSE-1 was the earliest in day of tasseling (44.33 days from planting) and days to silking (45.66 days from planting). NTS-2 was the highest in husked ear diameter (48.49 mm), while HAV-3 pocessed the highest Total Soluble Solids concentration (15.26%). Inbred TSST produced the tallest plants (230 cm) and had the highest ear placement (125.63 cm). All these inbred lines (FTT-1, HSE-1, HAV-3 and TSST) had superior characteristics making them potential for further development of hybrid varieties. High estimates of broad-sense heritability (h2B) was obtained on dehusked ear yield with heritability of 77.79%, followed by number of kernels per row (77.08%), dehusked ear weight (75.82%), number of kernel rows per ear (75.08%), husked ear yield (68.14%), dehusked ear length (67.81%), husked ear weight (67.47%), ear height (61.55%) and plant height (60.94%). Simple correlation coefficients based on agronomic characteristics show that husked ear yield was highly positively correlated with dehusked ear yield, husked and dehusked ear weight, dehusked ear length, husked and dehusked ear diameter, number of kernels per row and plant height (r= 0.931, 0.996, 0.928, 0.688, 0.842, 0.790, 0.775 and 0.531, respectively), while positively correlated with husked ear length, total soluble solids concentration and ear height (r= 0.398, 0.449 and 0.428, respectively). The lowest genetic distances was between HAW-4 and NTS-2 (normalize average Euclidean= 0.336), while inbred TSST (1.926 dissimilarity coefficients) had high genetic differentiation. The outcome from this morphological evaluation can be further complete with molecular marker analysis to reveal the variation among the inbred lines at DNA level, so that the precise selection can be made for production of superior hybrid varieties in Malaysia.